Improvement of the Cycling Performance and Thermal Stability of Lithium-Ion Cells by Double-Layer Coating of Cathode Materials with Al2O3 Nanoparticles and Conductive Polymer - Lee, Yoon-Sung; Shin, Won-Kyung; Kannan, Aravindaraj G.; Koo, Sang Man; Kim, Dong-Won (American Chemical Society, 2015)
We demonstrate the effectiveness of dual-layer coating of cathode active materials for improving the cycling performance and thermal stability of lithium-ion cells. Layered nickel-rich LiNi0.6Co0.2Mn0.2O2 cathode material was synthesized and double-layer coated with alumina nanoparticles and poly(3,4-ethylenedioxythiophene)-co-poly(ethylene glycol). The lithium-ion cells assembled with a graphite negative electrode and a double-layer-coated LiNi0.6Co0.2Mn0.2O2 positive electrode exhibited high discharge capacity, good cycling stability, and improved rate capability. The protective double layer formed on the surface of LiNi0.6Co0.2Mn0.2O2 materials effectively inhibited the dissolution of Ni, Co, and Mn metals from cathode active materials and improved thermal stability by suppressing direct contact between electrolyte solution and delithiated Li1-xNi0.6Co0.2Mn0.2O2 materials. This effective design strategy can be adopted to enhance the cycling performance and thermal stability of other layered nickel-rich cathode materials used in lithium-ion batteries.